PEMAHAMAN GURU TERHADAP INDIKATOR STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN: FAKTA DAN HARAPAN - Solehudin, Muhamad Dikdik; Rochman, Chaerul; Farida, Ida; Hadiana, Eri (Universitas Esa Unggul, 2020)
AbstractThis study discusses to discuss the attainment of standard indicators of PAI and Non-PAI teachers and education personnel, with regard to 19 indicators of educator and education staff standards. In this research quantitative descriptive methods, data collection using questionnaire techniques, and data analysis. The questionnaire was distributed via Google from 5 PAI teachers and 5 Non-PAI teachers. Collect agreed data and triangulate the results of interviews with several teachers and analyze the results of participation between PAI and Non-PAI teachers. The results showed an understanding of the standard of educators and education personnel at 84.50% for PAI teachers and 83.70% for Non PAI teachers. This shows the level of success of the Standard of educators and education staff through the understanding of respondents through each indicator is still lacking, so this needs to be improved by educators and education staff.Ã‚Â Keywords: teacher understanding, educator standards & education personnel.Ã‚Â AbstrakPenelitian ini bermaksud untuk mengetahui perbandingan ketercapaian indikator standar pendidik dan tenaga kependidikan guru PAI dan Non-PAI, dengan memperhatikan 19 indikator dari standar pendidik dan tenaga kependidikan. Dalam penelitian ini digunakan metode kuantitatif deskriptif, pengumpulan data dengan teknik angket, dan analisis data. Angket disebar melalui google form kepada 5 guru PAI dan 5 guru Non-PAI. Mengumpulkan data otentik dan triangulasi hasil wawancara dengan beberapa guru dan menganalisisÃ‚Â hasil perbandingan antara guru PAI dan Non-PAI. Hasil penelitian menunjukkan perbandingan pemahaman standar pendidik dan tenaga kependidikan sebesar 84,50 % untuk guru PAI dan 83,70 % untuk guru Non PAI. Hal ini menunjukkan tingkat pencapaian Standar pendidik dan tenaga kependidikan melalui pemahaman responden melalui setiap indikatornya masih kurang, maka hal ini perlu ditingkatkan oleh pendidik dan tenaga kependidikan.Ã‚Â Kata kunci: pemahaman guru, standar pendidik & tenaga kependidikan